2021
DOI: 10.3758/s13414-021-02295-0
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Prioritization Effect: Self-referential processing in movement highlights modulation at multiple stages

Abstract: A wealth of recent research supports the validity of the Self-Prioritization Effect (SPE)—the performance advantage for responses to self-associated as compared with other-person-associated stimuli in a shape–label matching task. However, inconsistent findings have been reported regarding the particular stage(s) of information processing that are influenced. In one account, self-prioritization modulates multiple stages of processing, whereas according to a competing account, self-prioritization is driven solel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 102 publications
(264 reference statements)
3
24
0
Order By: Relevance
“…Additionally, increasing evidence from the neuroscience literature and lesion-patient studies suggests that self-prioritization advantages arise independently of the depth of semantic encoding and semantic classification ability (Grilli & Glisky, 2013;Grilli & McFarland, 2011;Rathbone et al, 2011;Sui & Humphreys, 2013b). Lastly, our results in the first analysis demonstrate that the SPE we observe in the present sample affects both perceptual and decisional levels of information processing, supporting the suggestion that SPEs arise at multiple levels of information processing (Cunningham & Turk, 2017;Desebrock & Spence, 2021;Golubickis et al, 2018;Hu et al, 2020;Sui & Humphreys, 2017b). However, given that self-prioritization influences various levels of information processing, the present results do not allow us to draw certain conclusions about whether the intraindividually stable SPE relates to individual-specific, trait-like differences in a single processing level (e.g., perception, memory), or whether it results from the integrated processing across different hierarchical levels.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Additionally, increasing evidence from the neuroscience literature and lesion-patient studies suggests that self-prioritization advantages arise independently of the depth of semantic encoding and semantic classification ability (Grilli & Glisky, 2013;Grilli & McFarland, 2011;Rathbone et al, 2011;Sui & Humphreys, 2013b). Lastly, our results in the first analysis demonstrate that the SPE we observe in the present sample affects both perceptual and decisional levels of information processing, supporting the suggestion that SPEs arise at multiple levels of information processing (Cunningham & Turk, 2017;Desebrock & Spence, 2021;Golubickis et al, 2018;Hu et al, 2020;Sui & Humphreys, 2017b). However, given that self-prioritization influences various levels of information processing, the present results do not allow us to draw certain conclusions about whether the intraindividually stable SPE relates to individual-specific, trait-like differences in a single processing level (e.g., perception, memory), or whether it results from the integrated processing across different hierarchical levels.…”
Section: Discussionsupporting
confidence: 83%
“…Both tasks rely partly on different sets of cognitive processes (Golubickis & Macrae, 2021; Janczyk et al, 2019), such as lexical processing, higher memory load, and conceptual mapping in shape-label matching compared to categorization. Furthermore, as self-prioritization emerges across multiple levels of processing (Desebrock & Spence, 2021; Janczyk et al, 2019; Sui, 2016) it is not clear whether the SPE measured via both tasks is directly comparable and derives from the influence of the same central self-representational aspects.…”
Section: Present Studymentioning
confidence: 99%
“…While the functional role of self-prioritization is well placed in the adaptive context, there is less consensus regarding its mechanistic generation. While accumulating neuropsychological and behavioral evidence suggests that self-related behavioral facilitation arises across multiple stages of information processing, the contribution of the different processing stages, particularly perceptual processing (Macrae et al, 2017; Reuther & Chakravarthi, 2017; Siebold et al, 2015; T. Stein et al, 2016; Sui et al, 2012), is still debated (Caughey et al, 2021; Constable, Welsh, et al, 2019; Constable et al, 2011; Conway & Pleydell-Pearce, 2000; Cunningham et al, 2008; Desebrock & Spence, 2021; Frings & Wentura, 2014; Golubickis et al, 2021; Sui & Humphreys, 2013).…”
Section: Does Self-relevance Modulate “Perception”? the Need For A Cl...mentioning
confidence: 99%
“…This provides further evidence for the tripartite model of self-construal theory. Researchers found that people can also rapidly tag neutral actions with a personal association, thereby making their behavior toward the self more efficient ( Frings and Wentura, 2014 ; Moradi et al, 2018 ; Desebrock and Spence, 2021 ). Combined with our finding, all three selves have a self-prioritization effect, and can be tagged with neutral actions, which would fit the idea of an organism attuned to self-survival at multiple processing levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies ( Enock et al, 2018 ; Desebrock and Spence, 2021 ) propose a signal detection approach calculated using a sensitivity index (d prime, d’) was instead of the traditional accuracy. Hits were coded as correct responses for matching conditions and false alarms were coded as incorrect responses for mismatching conditions.…”
Section: Methodsmentioning
confidence: 99%